2009
DOI: 10.1108/17473610910964732
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of young Chinese customers' online shopping behaviors and service quality perceptions

Abstract: Purpose -This paper seeks to use the consumer-perceived levels of internet shopping skills and challenges, to cluster the young Chinese customers and to compare the quality perceptions of customers from the different clusters.Design/methodology/approach -A survey of 237 college students from Beijing with the average age of 20.2 was conducted via a paper-and-pencil questionnaire. All the constructs were measured using established scales. The students completed the questionnaire in their native language.Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Unlike traditional physical shopping environments, the online shopping environment integrates the entire sales process in a single platform (Mummalaneni and Meng, 2009). Free…”
Section: Attitude Towards Online Shopping and Purchase Intentionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike traditional physical shopping environments, the online shopping environment integrates the entire sales process in a single platform (Mummalaneni and Meng, 2009). Free…”
Section: Attitude Towards Online Shopping and Purchase Intentionsmentioning
confidence: 99%
“…Unlike traditional physical shopping environments, the online shopping environment integrates the entire sales process in a single platform (Mummalaneni and Meng, 2009). Free of geographic and temporal boundaries, consumers benefit from increased convenience through online shopping.…”
Section: Attitude Towards Online Shopping and Purchase Intentionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Connolly and Bannister (2008) noted differences between countries in usage of egovernment services, and Rotchanakitumnuai (2008) found such services less generally accepted in developing economies. Furthermore, the cross-cultural perceptions of service quality can be affected by socio-economic differences (Mummalaneni and Meng, 2009). Parasuraman et al (2005) found differences between users in definitions of technological terms such as 'technology readiness', which may affect evaluations of e-service quality.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the interactions between customers and retailers' websites, through which customers can search necessary information, and place their orders. Most conceptualization of web-based service quality was based on the adaptation of the SERVQUAL model, which has been examined intensively during the past two decades (Mummalaneni and Meng, 2009). However, SERVQUAL does not embrace the unique facets of online service quality, such as customer-to-website interactions (Cai and Jun, 2003).…”
Section: B Service Quality In the E-commerce Contextmentioning
confidence: 99%